Estado nutricional, qualidade da dieta e marcadores inflamatórios de risco para doenças crônicas não transmissíveis em adolescentes de São Luís – MA. - MATIAS, Nádia Caroline de Moura (2019)
INTRODUCTION: Unhealthy eating habits are increasingly associated with the risk of developing overweight and chronic noncommunicable diseases (CNCDs). Inflammatory markers associated with CNCD may already be altered even in childhood and adolescence. OBJECTIVE: To evaluate the relationship between nutritional status, diet quality and inflammatory markers in adolescents enrolled in public schools in São Luís-MA. METHODS: This was a cross-sectional study of 384 adolescents between 17 and 18 years of age. The nutritional status was evaluated through the Body Mass Index (BMI). The Revised Diet Quality Index (IQD-R) was used to evaluate the quality of the adolescents' diet. The inflammatory markers used were Ultrasensitive C-Reactive Protein (hs-CRP), IL-6 (Interleukin-6) and TNF-α (Tumor Necrosis Factor α). To evaluate the relationship between the anthropometric index, diet and inflammatory markers, a multivariate analysis was performed using the Decision Tree using the CART (Classification and Regression Tree) algorithm. RESULTS: The mean age was 17.3 years (SD ± 0.5) and there were predominance of female adolescents (56.5%) and eutrophic (69.3%). The mean IQD-R score was 55.3 (SD ± 12.7) and 32.0% were classified as inadequate diet, 65.6%, with a diet requiring modification and only 2.4% with a healthy diet. Adolescents in the lowest tertile of IQD-R (T1) had a higher mean BMI (22.1 ± 4.3kg / m2 vs 21.5 ± 3.7kg / m2). Higher levels of IL-6 were observed in those located on the IQD-R T1 (1,345 mg / L vs 1,205 mg / L). In the same group (T1), adolescents who had higher IL-6 levels also had a higher mean BMI (23.6 ± 5.1 kg / m2 vs 20.8 ± 3.0 kg / m2). The adolescents in the largest tertiles of IQD-R (T2 and T3) and who had higher concentrations of IL-6 and hs-CRP had also a higher mean BMI (23.8 ± 4.9 kg / m2). CONCLUSION: The diet quality of adolescents studied needs to be modified. BMI averages appear to be influenced by diet quality and serum levels of IL-6 and us-CRP.